Monetary Policy Transmission And Exchange Rate Fluctuations In Asian Countries - Laila Adamy; Lia Nazliana Nasution; Rusiadi Rusiadi; Bhaktiar Efendi; Suhendi Suhendi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study investigates the effectiveness of monetary policy instruments—money supply, interest rates, and foreign exchange reserves—in managing trade balance stability across selected Asian and European countries, including Indonesia, India, the United Kingdom, and Russia. Employing a quantitative approach with a Panel Autoregressive Distributed Lag (ARDL) model, the research examines both shortterm and longterm effects of macroeconomic variables on trade performance from 2019 to 2023. The findings reveal that in Indonesia and India, money supply and interest rates serve as primary indicators for maintaining external equilibrium, aligning with classical monetary theory. In contrast, foreign exchange reserves are the sole significant factor influencing trade balance stability in Russia and the UK. The panel analysis confirms that while all variables contribute, interest rate is the most consistent tool for longterm trade balance management, whereas reserves and interest rate dominate in the short term. These results underscore the need for adaptive, contextspecific policy combinations rather than reliance on a single instrument. The study offers strategic insights for policymakers in emerging markets, highlighting the critical role of coordinated monetary tools in ensuring macroeconomic and external sector resilience.